Poskusi prevrednotenja položaja Ruske federacije v mednarodni skupnosti - primer Gruzije - Udovič, Boštjan (Družboslovne razprave, 2009)
The international political events that took place in the southern Caucasus in August 2008 call for an in-depth analysis of their causes. The geographical area of the former Soviet Union was subjected to tectonic changes in geo-political affairs which consequently had a weakening effect on the role of Russia and its sphere of interest. The article contends that Russia made good use of the political changes in Georgia and Ukraine, trying to reposition itself particularly towards the United States of America and the European Union. The latter is made clear in various activities of Russian foreign policy vis-a-vis other countries of the former Soviet Union during the last eight years. The article concludes by confirming our thesis that Russia has achieved a revaluation of its position by using economic means of foreign policy and will continue to do so in the future since there is a clear desire and idea in Russia that the Russian Federation must reinstate the position it enjoyed under the 45-year rule of the former Soviet Union.
Keywords: International relations; Mednarodni odnosi; Foreign policy; Zunanja politika; International community; Mednarodna skupnost; Rusija; Russia; Georgia; Gruzija; economy; gospodarstvo